1979
DOI: 10.1007/bf01200901
|View full text |Cite
|
Sign up to set email alerts
|

Nonchromaffin paraganglioma of the duodenum

Abstract: A benign nonchromaffin paraganglioma of the duodenum is described and compared with other reported cases. Duodenal location is extremely rare but the morphology, based on the optical microscopic pattern (Zellballen) and the ultrastructural appearance is, comparable with paragangliomas of other sites. The lack of nerve fibres and ganglion cells in this tumour, together with the absence of a positive chromaffin reaction permits us to classify it as a pure nonchromaffin paraganglioma. This finding constitutes ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The presence of three such distinctive histologic patt erns , admixed to varying degrees, led Kepes and Zach arias (14) to label the se duodenal tumors as gangliocy tic paragangliomas. This term has been widely applied to this group of neopl asms, and we a re awar e of onl y a s ingle pa ragangliom a th at lack ed gangliocytic elements, yet arose in this location (9). Qizilba sh indicated that small numb ers of ganglion cells and the fre quent admixture of carcinoid al elements are quit e charac teristic of the se duod enal lesion s (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of three such distinctive histologic patt erns , admixed to varying degrees, led Kepes and Zach arias (14) to label the se duodenal tumors as gangliocy tic paragangliomas. This term has been widely applied to this group of neopl asms, and we a re awar e of onl y a s ingle pa ragangliom a th at lack ed gangliocytic elements, yet arose in this location (9). Qizilba sh indicated that small numb ers of ganglion cells and the fre quent admixture of carcinoid al elements are quit e charac teristic of the se duod enal lesion s (15).…”
Section: Discussionmentioning
confidence: 99%
“…One theory ascribes their origin to persistent fetal paraganglia (9,12,20). Other s have sugges ted that they originate from the celiac ganglion (13) or from part of the intravagal paraganglionic system (9,21). Although neur al crest migration has been a popul ar notion (5,10,12,16,18,20), perh aps the most attractive theory is the one that suggests an origin from a plurip otential cr ypt ste m ce ll capable of multi-directional differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There was also some confusion regarding ganglioneuromatosis, which is a component of multiple endocrine neoplasia type 2b. Pure nonchromaffin paragangliomas of the duodenum are also very rare [2]. On the other hand, sympathetic paraganglioma rarely involved the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical locations in the head and neck include nose and paranasal sinuses, orbit [Deutsch and Duckworth, 1969], larynx [Tobin and Harris, 1972], and the thyroid gland [Kay et al, 1975]. In addition PGLs also occasionally occur in other regions of the body such as mediastinum [Moran et al, 1993], thorax, retroperitoneum, stomach, duodenum [Matilla et al, 1979], urinary bladder [Spitzer et al, 1971], and uterus [Young and Thrasher, 1982]. For the most part PGLs arise during adulthood with a wide range of patients' age at disease onset [Grufferman et al, 1980;van der May et al, 1989].…”
Section: Introductionmentioning
confidence: 99%